Efektivitas Kombinasi Tablet Tambah Darah dengan Jeruk Manis dalam Meningkatkan Kadar Hemoglobin: The Effectiveness of Combining Iron Supplementation with Sweet Orange in Increasing Hemoglobin Levels - Sihotang, Urbanus; Sinaga, Nora Martis; Nasution, Erlina (Amerta Nutrition, 2025)
Background: Iron (Fe) deficiency is the leading cause of anemia worldwide due to the impact on hemoglobin (Hb) production. Meanwhile, several nutrients, including protein, iron, copper (Cu), zinc (Zn), vitamin A, and vitamin C, influence Hb levels. Objective: This study aimed to evaluate the effectiveness of iron supplementation combined with sweet orange in increasing Hb levels. Methods: A quasi-experimental pretest-posttest design was used with a total of 45 menstruating female students from Grades 8 and 9 as participants. These individuals were divided into two groups, one group received iron supplements (TTD) alone, while the other was given TTD combined with 130 grams of sweet orange, providing 63.7 mg of vitamin C, for 12 weeks. Hb levels before and after the intervention were measured using the Easy Touch GCHb device. An independent t-test was used for statistical analysis. Results: The results showed that the combination of TTD and vitamin C from sweet orange was significantly more effective in increasing Hb levels in adolescents compared to TTD alone (p-value=0.001). Conclusions: The combination of TTD and sweet orange was more effective in increasing Hb levels. These results provide valuable insights for government programs aimed at improving adolescent iron supplementation by incorporating vitamin C-rich food sources, such as sweet orange, to enhance iron absorption.